Complement Component C3 Variant (R102G) and the Risk of Neovascular Age-Related Macular Degeneration in a Tunisian Population - Habibi, Imen; Sfar, Imen; Kort, Fedra; Bouraoui, Rim; Chebil, Ahmed; Limaiem, Rim; Ayed, Saloua; Ben Abdallah, Taïeb; El Matri, Leila; Gorgi, Yousr (Klinische Monatsblatter fur Augenheilkunde, 2017)
To explore the association between the polymorphism (S/F) p.R102G in the C3 gene and age-related macular degeneration (AMD) in a Tunisian population. The molecular study was performed by polymerase chain reaction using sequence-specific primers (PCR-SSP) in 207 control subjects free of any eye disease (fundus normal) and 145 patients with exudative AMD. The activity and quantification of and have been made by technical home method and nephelometry, respectively. The prevalence of GG genotype polymorphism was significantly higher in AMD patients compared to controls (OR: 2.41, IC 95% [1.90-3.05], p = 0.0007). However, no correlation was found between this allelic variant and the type of neovascularization. Similarly, there is no association between this polymorphism and the presence of functional and/or quantitative hypocomplementemia. The GG genotype of the gene could be a susceptibility factor for AMD in the Tunisian population. However, it does not seem to influence the clinical profile of the disease.